Upaya Meningkatkan Hasil Belajar PKN Materi Pancasila Sebagai Ideologi Terbuka Melalui Keterampilan Berpikir Kritis Dengan Model Pembelajaran Studi Kasus Pada Siswa Kelas XII MIA-4 SMAN 1 Peukan Bada Aceh Besar Semester Ganjil Tahun Pelajaran 2019/2020 - Sariya (Journal of Technology and Literacy in Education, 2022)
This research was conducted using a critical thinking learning model for Civics subjects in Pancasila as an Open Ideology for class XII.MIA-4 students of SMAN 1 Peukan Bada in the 2019/2020 school year with 20 students as research subjects. KKM is set at 75 and classical completeness is at least 85%. The daily scores obtained by students are still below the KKM with an average of 68.50. and classical completeness 20%. In the application of the case study learning model from cycles I to II, students’ critical thinking skills have been seen in analyzing problems, looking for alternative solutions, and making decisions during group discussions and class/panel discussions. In addition, the activeness of students in expressing opinions, asking questions and even refuting the opinions of their friends properly and systematically. With direct or indirect interactions between teachers and students and between students and students. After carrying out the first cycle of action, an average score of 72.25 was obtained for 12 students or 60%. 8 students who have not completed or 40%, in the second cycle the average value of 80.00 completed 100%, it can be concluded that the use of the learning model through the case of students can think critically and can improve learning outcomes very significantly.